THE EXPLORATION OF TEACHER LEADERSHIP AT SECONDARY SCHOOLS IN KAZAKHSTAN - Khoroshash, Aidar (Graduate School of Education, 2016)
Despite the vast amount of research about educational leadership found in international literature, Kazakhstan has not yet developed an extensive discussion about leadership in education, including teacher leadership. This study explores teacher leadership at secondary schools in Kazakhstan, looking specifically at how important it is for Kazakhstani education to promote its teachers as leaders. Various stakeholders from two local schools such as principals, vice-principals, teachers and students were surveyed and interviewed to identify their perceptions of teacher leadership in both theory and practice, and also to understand what either facilitates or challenges teacher leadership in this country. Because Kazakhstani education is still connected to its Soviet Union heritage, the interviewed administrators and teachers were questioned about whether a typical Soviet school would have any elements of leadership, in order to relate them to the current situation in independent Kazakhstan. An analysis of the main findings yielded the stakeholders‘ own explanations that teacher leadership is a rare case in schools, since teachers lack the chance to extend their understanding of leadership. As a result of such a poor level of knowledge, teachers miss an opportunity to develop leaderful practices in and outside their schools because of the topdown tradition and highly hierarchical relationships still inherent in the system. The `Soviet` leadership, often associated with `high moral values` by veteran teachers, remains deeply embedded in the minds of many, while others blame Communism for its false proclamations and ideology in education. The findings ultimately suggested that re-orienting the current system from top-down to shared governance should both reconcile the schools with the Ministry of Education and empower teachers in Kazakhstan to actively participate and voluntarily commit themselves to change and reform in the country. With such major implications drawn from the findings, this project will contribute to current and future research on teacher leadership in Kazakhstan.
Keywords: Type of access: Restricted; perceptions; schools; Soviet ideology; stakeholders; teacher leadership